2021
DOI: 10.1080/02699931.2021.1916442
|View full text |Cite
|
Sign up to set email alerts
|

Having no words for feelings: alexithymia as a fundamental personality dimension at the interface of cognition and emotion

Abstract: This special issue brings together two important reviews and seven cutting-edge empirical papers concerning the influence of alexithymia on cognitive and emotional processing. Alexithymia is a multifaceted construct that is characterised by difficulties identifying one's feelings; difficulties describing one's feelings to others; and an externally focused, utilitarian cognitive style. In this paper, we begin by considering how emotion science has evolved in its understanding of personality traits, before highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 95 publications
(148 reference statements)
1
20
0
Order By: Relevance
“…Alexithymia reflects deficits in the regulatory processes of emotion and cognitive processing ( Luminet et al, 2021 ; Taylor and Bagby, 2021 ). Cognitive emotion regulation reflects both the cognitive and regulatory characteristics of emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia reflects deficits in the regulatory processes of emotion and cognitive processing ( Luminet et al, 2021 ; Taylor and Bagby, 2021 ). Cognitive emotion regulation reflects both the cognitive and regulatory characteristics of emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, alexithymia might lead to invalid and inflexible emotional regulation modes and become a risk factor for various physical and mental disorders ( Luminet et al, 2021 ), Bonnaire et al (2013) and Morie et al (2016) suggested that alexithymia may have a critical role in the pathogenesis of substance use disorders, behavioral addiction, and Internet addiction. Dalbudak et al (2013) , Lyvers et al (2016) , and Schimmenti et al (2017) found that the level of alexithymia was higher in the Internet addiction group than in the normal group, and that there is a significantly positive correlation between Internet addiction and alexithymia.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia is a relatively stable and negative personality trait that manifests as low emotional awareness and operational thinking. These are more likely to produce rigid and inflexibility thinking patterns ( Taylor and Bagby, 2021 ) in the individual, make him/her more prone to suppressive regulation strategies rather than reappraisal strategies ( Swart et al, 2009 ), and trigger poor internal monitoring and avoidance behavior ( Luminet et al, 2021 ). Due to different types of metacognitive processing mentioned in the S-REF model, such as the aforementioned characteristics, individuals have two very different cognitive processing modes, namely, object mode and metacognitive mode.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia is a mental condition characterized by difficulties identifying and describing one’s own feelings, externally oriented thinking, and limited imaginative capacity [ 23 ]. The majority of research has approached alexithymia as a stable personality trait, thought to be developmental in nature, reflecting a lack in emotion regulation and cognitive processing [ 24 ]. Awareness of one’s own emotions can prevent us from primitive, uncontrolled emotional responses when facing negative events.…”
Section: Introductionmentioning
confidence: 99%